Peran Kantor Badan Pertanahan Nasional Mengenai Hak Kepemilikan Atas Tanah Di Kota Jakarta Utara - Risye Julianti; Soefyanto Soefyanto; M Yasir (JOURNAL of LEGAL RESEARCH, 2021)
The purpose of this research is to determine the legal implications of the National Land Agency's actions, which resulted in overlapping land ownership rights in North Jakarta. The research method used is Juridical Empirical, which involves analyzing narrative data in the form of statements and then conducting searches for regulations related to this research based on legislation. The results of this research are in the form of collecting and researching juridical data and physical data on land parcels which must be thoroughly investigated, especially regarding land history based on Law Number 5 of 1960 concerning the Basic Agrarian Law. As for those who do not have a certificate, the information on land ownership must be accurate, and after that the data will be announced to the public at the Office of the National Land Agency for the North Jakarta City Administration, the location of the land in question to provide opportunities for interested parties.Keywords: Overlap; Ownership of land rights; National Land Agency.